2020
DOI: 10.1016/j.acra.2020.04.030
|View full text |Cite
|
Sign up to set email alerts
|

18FDG PET/CT Scan Reveals Hypoactive Orbitofrontal Cortex in Anosmia of COVID-19

Abstract: During the current nascent pandemic, anosmia has been increasingly reported among patients with coronavirus disease-2019 (COVID-19) (1). While postviral olfactory loss secondary to nasal congestion or conductive pathway alteration is a known sequela of sinonasal viral infections (2), anosmia of COVID-19 is less commonly associated with rhinorrhea or nasal congestion (3). This may indicate sensory neural loss as the underlying cause of the olfactory dysfunction rather than the conductive mechanism in most cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
2
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 8 publications
3
86
2
8
Order By: Relevance
“…Therefore, there could be a direct contact and interaction with a possible cytopathic effect of SARS-CoV-2 on ACE2-expressing neurosensory receptor cells [28]. Given the prevalence of hyposmia in COVID-19 and the higher frequency in non-severe patients that appears in our study, damage to olfactory receptors in the epithelium of the nasal mucosa or in the olfactory bulbs seems more likely than central cortical involvement [25].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, there could be a direct contact and interaction with a possible cytopathic effect of SARS-CoV-2 on ACE2-expressing neurosensory receptor cells [28]. Given the prevalence of hyposmia in COVID-19 and the higher frequency in non-severe patients that appears in our study, damage to olfactory receptors in the epithelium of the nasal mucosa or in the olfactory bulbs seems more likely than central cortical involvement [25].…”
Section: Discussionmentioning
confidence: 64%
“…Four reports of the findings on nasal cavity and brain magnetic resonance imaging (MRI) in patients with COVID-19 and sudden olfactory loss found various results: no abnormality [21], bilateral obstructive inflammation of olfactory clefts without anomalies of the OB and tracts [22], bilateral transient OB edema [23], and transient cortical hyperintensity in the right gyrus rectus and in the OB [24]. Furthermore, a report of a decreased metabolic activity in the orbitofrontal cortex on a 18− FDG PET/CT scan of a patient with COVID-19-related anosmia suggested that there could be an impaired neural activity in olfactory pathways despite normal morphology [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this era, a unique advantage of whole-body PET/CT over competing for imaging modalities is the potential for detection of additional incidental metabolically active lesions throughout the rest of the body in a single acquisition. Karimi et al 18 (no. 34) have reported reduced activity in the orbitofrontal cortex in COVID-19-associated anosmia, which might indicate an impaired neural function as the underlying pathology of anosmia, due to SARS-CoV-2 neurotropism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we reported one patient in our center ( Fig. 2 ) and a series of PET/CT images from three included studies 16 , 17 , 18 via formal permissions obtained from their publishers. ( Fig 3 - 5 )
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation